TINJAUAN HUKUM PENCEMARAN LAUT LINTAS BATAS AKIBAT TUMPAHAN MINYAK DARI TABRAKAN KAPAL BERDASARKAN THE 1992 PROTOCOL OF THE INTERNATIONAL CONVENTION ON CIVIL LIABILITY FOR OIL POLLUTION DAMAGE 1969 - Fivian Army; Maria Maya Lestari; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Malacca Strait is one of the routes in the cross-border oil trade which often experiences marine pollution due to ship collisions. The sea polluted by the oil spill will have a negative effect on various marine organisms and result in fishermen and surrounding communities experiencing economic losses. So, we need an international law that regulates compensation for victims of oil pollution by ships at sea where one of the international conventions that regulates is The 1992 Protocol of the International Convention on Civil Liability for Oil Pollution Damage 1969.This type of research is normative research, where this research uses a research methodology on the principles of international law. Research on legal principles is carried out on legal rules. Research on legal principles is a philosophical research, because legal principles are an ideal element of law. The data sources used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials, the data collection technique in this study is the literature review method, after the data is collected then analyzed to draw conclusions.From the results of the research, it was found that, First, The 1992 Protocol of the International Convention on Civil Liability for Oil Pollution Damage 1969 stipulates that if oil leaking from a ship causes damage to the territory or territorial sea of one of the members of the convention, the ship owner is absolutely responsible. Legally for the damage, which means that it includes both the cost of preventive measures and the loss or further damage caused by the action which has been stipulated in Article 5 of the 1992 CLC Protocol. The author's suggestion is that the participating countries that are members of the IMO and the participants of the 1992 CLC and/or the 1992 Fund Convention, in order to clarify the limits and provisions that limit the types of losses that can be claimed for compensation.Keywords: Ship collision - Oil - Sea Pollution